2014
DOI: 10.1007/s11356-014-3046-x
|View full text |Cite
|
Sign up to set email alerts
|

Support vector machine―an alternative to artificial neuron network for water quality forecasting in an agricultural nonpoint source polluted river?

Abstract: Water quality forecasting in agricultural drainage river basins is difficult because of the complicated nonpoint source (NPS) pollution transport processes and river self-purification processes involved in highly nonlinear problems. Artificial neural network (ANN) and support vector model (SVM) were developed to predict total nitrogen (TN) and total phosphorus (TP) concentrations for any location of the river polluted by agricultural NPS pollution in eastern China. River flow, water temperature, flow travel ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…Each ðx i ; O i Þ whose corresponding α i and α Ã i are nonzero and contribute to the SVR function are known as support vectors (SVs). There are various kernel functions, but this paper adopts the radial basis function, which is the most commonly used kernel function and is the best at modeling nonlinear relations (Hsu et al 2003;Liu and Lu 2014). The radial basis function k RBF is defined as…”
Section: Support Vector Regressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Each ðx i ; O i Þ whose corresponding α i and α Ã i are nonzero and contribute to the SVR function are known as support vectors (SVs). There are various kernel functions, but this paper adopts the radial basis function, which is the most commonly used kernel function and is the best at modeling nonlinear relations (Hsu et al 2003;Liu and Lu 2014). The radial basis function k RBF is defined as…”
Section: Support Vector Regressionmentioning
confidence: 99%
“…The MAE measures the mean of the magnitudes of all residual errors between the modeled (y i ) and observed (O i ) values of the dependent variable (BOD). Bias represents the mean of all residual errors (Liu and Lu 2014), indicating the extent to which the modeled values overestimate or underestimate the dependent variable. The R 2 (of regression) measures the percentage of data variability explained by the modeled values and the goodness of fit, ranging 0 to 1 (zero correlation to a perfect match between the modeled and observed values).…”
Section: Model Performancementioning
confidence: 99%
See 2 more Smart Citations
“…They observed that this method was effective in predicting water quality categories that are based on the US Salinity Laboratory diagram. Liu and Lu (2014) predicted water quality of rivers by estimating total nitrogen and total phosphorus using SVM and NN approaches and observed that SVMs provided higher accuracy results.…”
Section: Data Science Methodsmentioning
confidence: 99%